POTENTIAL ANALYSIS OF LEADING ECONOMIC SECTOR IN ECONOMIC DEVELOPMENT IN NGANJUK REGENCY - Audyra Gusti Putri; Sri Indah Nikensari; Dicky Iranto (Transpublika Publisher, 2022)
This research aims to analyze the leading economic sectors that can support economic development in Nganjuk Regency, the base and non-base sectors, the changing and shifting sectors, and the classification of growth sectors in order to determine the leading sectors in Nganjuk Regency. Gross Domestic Regional Product by Business Field Based on Constant Price in 2018-2021 in Nganjuk Regency and East Java is utilized in this study. The information is obtained from Statistics Indonesia. This study employs a descriptive quantitative methodology. This research utilizes Location Quotient, Shift Share, and Typology Klassen for analysis. Location Quotient has determined that there are eight base sectors and nine non-base sectors. The base sectors are also the leading economic sector in Nganjuk Regency's economic development. In addition, according to the results of Shift Share, fifteen economic sectors have positive growth. In addition, there are nine sectors with a progressive growth rate. The result of Typology Klassen is the division of seventeen economic sectors into four quadrants. There are three sectors in the first quadrant, seven sectors in the second quadrant, five sectors in the third quadrant, and two sectors in the fourth quadrant. Water Supply, Sewerage, Waste Management, and Remediation Activities are the leading economic sector according to all of the research's analysis methods. This sector is a base sector, has a positive percentage in each component of Shift Share and a positive Shift Share value, and is located in Quadrant I of the Typology Klassen.